Access to e-learning in Higher Education by Disabled Students: Current Public Policy Issues - Konur, Ozcan (Proceedings of the International Conference on Networked Learning, 2002)
The emerging public policy issues regarding access to networked learning in higher education by disabled students are presented to disseminate research based on a four-year long self-funded research project at City University. The networked learning has formed a main ingredient of the curriculum in the UK universities in recent years. Unsurprisingly, a substantial body of research emerged in this issue. In the meantime, disabled students continued to be under-represented with a participation ratio of 4.5 % with a differential rate of participation among inter-disability groups. The access to networked learning would be regulated by the Disability Discrimination Act (1995) as amended by the Special Educational Needs and Disability Act (2001) starting from September 2002. This paper disseminates research on the related public policy issues from an interdisciplinary research and policy perspective.